DAMPAK REMITAN EKONOMI TERHADAP POSISI SOSIAL BURUH MIGRAN PEREMPUAN DALAM RUMAH TANGGA - Asih Sulistiyo, Putri; Sri Wahyuni, Ekawati (Sodality: Jurnal Sosiologi Pedesaan, 2012)
The objectives of this study are to analyse the push-pull factor of international migration and the impact of economic re mittance s t o migrant  women’ s soc i al  posit i on  i n t he house hol d. Background of  i ts research is feminization of international migrant into line with the phenomenon of economic globalization. The magnitude economic remittances generate by the women migrants pre sumabl y wi ll  aff ect  women’ s social position in the houshold.  Culturally, women in this areas do not have a strong decision making power relative to the men in the household. The women migrant working abroad was mainly driven bThe women migrant working abroad was mainly driven b proverty. The return women migrant are likely to have stroger decision making power in the household be case of their major contribution in the household economy.   Keywords: woman migrant, social position, household.